2016
DOI: 10.1177/1087054712466917
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of the Relation Between Thyroid Functioning and Sluggish Cognitive Tempo in Children

Abstract: Although preliminary, results indicate that thyroid functioning may be related to SCT. Given the small effects, however, it is important for future research to examine other endocrine and biological correlates that may inform models of the developmental psychopathology of SCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Thyroid abnormalities are present in approximately 5% of children referred for ADHD 74 . Previously, Stein and Weiss 75 reported a greater proportion of lower Free Thyroxine Index (FTI) concentrations in children with ADHD-I, but not in children with ADHD-C, and there is also preliminary evidence that a higher concentration of serum thyroid stimulating hormone (TSH) is positively associated with SCT symptoms in children 76 . Examining the interrelations of SCT, ADHD, sleep, and endocrine functioning is an important direction for future research, particularly since hypothalamic-pituitary-adrenal (HPA) axis activity is associated with sleep problems as well as emotional and behavioral problems in children 77,78 .…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid abnormalities are present in approximately 5% of children referred for ADHD 74 . Previously, Stein and Weiss 75 reported a greater proportion of lower Free Thyroxine Index (FTI) concentrations in children with ADHD-I, but not in children with ADHD-C, and there is also preliminary evidence that a higher concentration of serum thyroid stimulating hormone (TSH) is positively associated with SCT symptoms in children 76 . Examining the interrelations of SCT, ADHD, sleep, and endocrine functioning is an important direction for future research, particularly since hypothalamic-pituitary-adrenal (HPA) axis activity is associated with sleep problems as well as emotional and behavioral problems in children 77,78 .…”
Section: Discussionmentioning
confidence: 99%
“…First, Becker et al (2017, this issue) found SCT symptoms, but not ADHD symptoms, to be related to thyroid functioning (as measured with thyroid stimulating hormone [TSH]). This association was found in a sample of children who had normative levels of TSH (though the sample was comprised of psychiatrically hospitalized children).…”
Section: Novel Preliminary Findingsmentioning
confidence: 99%
“…Three novel findings from studies in this Special Issue warrant brief mention in hopes that they will spur more research. First, Becker, Luebbe, Greening, Fite, and Stoppelbein (2017) found SCT symptoms, but not ADHD symptoms, to be related to thyroid functioning (as measured with thyroid stimulating hormone [TSH]). This association was found in a sample of children who had normative levels of TSH (though the sample was comprised of psychiatrically hospitalized children).…”
Section: Novel Preliminary Findingsmentioning
confidence: 99%
“…Becker et al [58] explicaron su estudio acerca de la relación entre los niveles de tirotropina y el TCL en 571 niños de 6-12 años. Sus análisis de regresión confirmaron la relación entre niveles de tirotropina y TCL, y no con TDAH, aunque la magnitud del efecto es baja.…”
Section: Desarrollounclassified